(untitled) (The Journal of Psychology and Sociology, 2017)
In this article, the authors present the results of a psychological research studying peculiarities of manifestation of basic emotions in different cultures. We studied and analyzed the manifestations of basic emotions on the example of the four ethnic groups (Kazakh, Tatar, German and Russian). The study sample amounted to students of fulltime and part-time department of Pavlodar State Pedagogical Institute in age from 18 to 30 years (N = 200). Among them: Russian – 50 people, the Germans – 50 people, the Kazakhs – 50 people, Tatars – 50 persons. With the help of computer-based testing for the detection of emotions we found that the degree of recognition of negative emotions (fear, anger, contempt, sadness and disgust); most typical Tatars and a little less Kazakhs, Germans and Russian; the degree of recognition of neutral and positive emotions (wonder, happiness) are most typical Germans and Kazakhs and a little less Tatars and Russian. As a result of the statistical analysis we did not found of statistically significant differences in the manifestation of basic emotions between the four nationalities, but we found cultural differences in the correlation analysis were found. We found a positive correlation (among Russian – between fear and sadness (0,744; р < 0,05); among Kazakhs – between joy and fear, anger and sadness (0,655; 0,870; р < 0,05); among Germans – between joy and fear (0,683; р < 0,05); among Tatars – between fear and sadness (0,853; р < 0,05) and negative correlation (among Germans – between anger and sadness (-0,635; р < 0,05). The interaction of these factors is a statistically significant. These results indicate that, living in the same city and are constantly interacting with each other, the representatives of different ethnic groups shows most often experienced emotions, and hence their recognition equally easily, regardless of the culture. At the same time, the effect of emotion on each other is different in different cultures. Key words: basic emotions, culture, cultural differences, fear, anger, wonder.